Evaluation and characterization of plasmids carrying CTX-M genes in a non-clonal population of multidrug-resistant Enterobacteriaceae isolated from poultry in Brazil - Ferreira, Joseane Cristina; Penha Filho, Rafael Antonio Casarin [UNESP]; Andrade, Leonardo Neves; Berchieri Junior, Angelo [UNESP]; Darini, Ana Lúcia Costa (Elsevier, 2016)
The increasing presence of ESBL-producing bacteria in food-producing animals might impact on public health. In this study, ESBL-producing enterobacteria were investigated in the microbiota of chickens produced in Brazil. We detected blaCTX-M-2, blaCTX-M-8 and blaCTX-M-15 in 13 Escherichia coli isolates, within 9 different PFGE-types. Escherichia fergusonii and Klebsiella pneumoniae were found carrying blaCTX-M-2. Plasmid Inc groups found included repF, FIB, FIC, I1, Y, B/O, A/C, K and HI1. F plasmids were present in 87.5% of the isolates, however, no resistance gene was harbored in this replicon. The pMLST for IncI1 showed ST113 and the novel ST130, ST131 and ST132 harboring blaCTX-M-8. IncK plasmids carried blaCTX-M-2 in one E. coli isolate. Non-typeable plasmids carrying blaCTX-M-2 or blaCTX-M-15 had up to 260 kb. blaCTX-M-2 was also associated with class I integron and ISCR1 and blaCTX-M-8 with IS10. Overall, similar resistance elements were disseminated among a diverse population of ESBL-producing enterobacteria.
Keywords: antimicrobial resistance; E. coli; ESBL; Plasmids; pMLST